MEDIA SOSIAL BAGI KEHIDUPAN DAN SISI GELAPNYA - Muhammad Fajar Febriyanto; Rangga Nur Alamsyah, Muhammad Fathi Robbani Mutawakkilin, Leonardo Siburian, Arie Nugroho, Andika Sy (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Social media has become an integral part of the daily lives of millions of people around the world. In addition to offering various benefits such as connectivity and access to information, social media also has a significant dark side. This article examines the influence of social media on life, including its positive effects, as well as the negative impact on mental health, social interaction, and the spread of misinformation. Through a literature review and analysis of recent data, this article aims to improve understanding of the benefits and risks associated with social media use and suggest mitigation strategies.